Allogeneic Platelet-Rich Plasma: At the Dawn of an Off-the-Shelf Therapy?. Issue 2 (February 2017) - Anitua, Eduardo; Prado, Roberto; Orive, Gorka
Abstract : A new therapeutic tool is emerging based on a biomimetic strategy: platelet-rich plasma (PRP) technology. Allogeneic off-the-shelf PRP represents a safe and cost-effective treatment for osteoarthritis and related diseases. This breakthrough opens the door not only to improved treatments and opportunities but also to new challenges with multiple uncertainties.